Analisis Sistem Pembelajaran Dalam Membangun Kompetensi Dan Kemandirian Siswa Berkebutuhan Khusus Di SKH Negeri 02 Kota Serang: Analysis of the Learning System in Building Competencies and Independence Among Students with Special Needs at State Special School No. 02 in Serang City - Sistriadini Alamsyah Sidik; Ilma Amalia; Risma Risma; Rd. Rizka Nabila; Dyessa Aprillya Febrianti; Agnes Puspita; Muslimah Muslimah; Najib Hibatullah; Stefany Damayanti (Paidagogia: Jurnal Pengajaran dan Pendidikan, 2025)
This study aims to analyze the learning system at SKH Negeri 02 Kota Serang in developing the competence and independence of students with special needs. The research uses a qualitative approach with literature analysis and direct observation at the school. The findings indicate that the application of constructivism theory, individualized learning, and the Montessori method can positively impact the development of students' competence and independence. However, there are still challenges such as limited facilities, the use of less interactive conventional teaching methods, and a lack of teacher training. This study concludes that despite the implementation of various approaches, improvements are needed in educational infrastructure and specialized teacher training. The development of more interactive methods and the use of diverse assistive technologies will support the enhancement of students' independence. This research is expected to contribute to the development of a more effective and responsive learning system for students with special needs.